Potencial de redução de emissões de gases de efeito estufa pela captura e sequestro de CO2 de destilarias de etanol do Centro Sul do Brasil para utilização em recuperação avançada de petróleo - Mattos, Thaís de Moraes (2018)
This study has developed a life cycle analysis (LCA) with the main objective to assess the GHG emissions of a project of bioenergy with carbon capture and storage (BIOCCS) that uses CO2 from the fermentation of ethanol distilleries from the CenterSouth of Brazil for use in Enhanced Oil Recovery (EOR) activities in the Campos Basin, showing the net emissions of CO2 storage after the subtraction of the emissions from the project´s implementation and operation, which are not usually considered. Three transportation options for CO2 were used, which were proposed in another study where the main purpose was an evaluation of the techonology with the minimum cost for different CO2 transportation networks, considering pipelines and trucks. This study showed that, differently from a financial point of view, where small distilleries showed to be favorable to road transport, this modal is a good choice for just one distillery when the full life cycle emissions are considered. The pipeline transportation to multiple Hubs showed to be the best option in terms of emissions. The phase that most contribute for emissions in the LCA is the transportation phase and the pipe manufacturing has the highest emission contribution in the LCA. The results from this study show that 444.7 MtCO2 are produced by the distilleries, but that it is still possible to achieve a net storage of 94.6% to 96.1% of that, since the emissions from this project´s life cycle analysis represent some 3.9% - 5.4% of that total in the three case studies considered.